Towards a semantic web of things framework - Nadim Ismai; El Ghayam Yassine; Abdelalim Sadiq (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
Information and communication teFchnologies (ICT) know a significant development especially in terms of hardware miniaturization, cost reduction and energy consumption optimization. This advancement enables the interconnection of a large number of physical objects namely using the Internet, forming what is called the Internet of Things (IoT). The IoT provides the opportunity to interact with these objects through sensors, actuators and smart applications which may help users in several areas such as transport, logistics, health care, agriculture, etc. However, building the IoT requires a strong interoperability between thousands of heterogeneous devices and services. In this context, the SWoT (Semantic Web of Things) uses semantic Web technologies to enrich these devices and services with semantic annotations which enables the semantic interoperability. However, the development of SWOT-based systems on a large scale faces many challenges especially due to the large number of devices and services, their geographical distribution as well as their mobility. These challenges-which may affect the system performance as a whole-require innovative industry and research efforts. The current paper proposes a SWoT framework architecture that take into account the main SWoT challenges.